2021
DOI: 10.1080/1369118x.2021.1963462
|View full text |Cite
|
Sign up to set email alerts
|

Digital divide and marginalized women during COVID-19: a study of women recently released from prison

Abstract: The COVID-19 pandemic has underscored the urgency to bridge the digital divide, as those without reliable internet, adequate devices, and digital literacy skills were severely disadvantaged when most essential activities moved online. This study examines how the pandemic has affected women recently released from jail or prison, a group that was already at a disadvantage in terms of digital access and skills even before the pandemic. Our interviews with 45 women in transition show that their lack of stable acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Figure 2 shows that most studies were published in 2020 (n = 7, 20%) [ 23 29 ] and 2021 (n = 6, 17%) [ 30 35 ]. Moreover, most of the studies were conducted in the United States (n = 11, 31%) [ 26 , 34 – 43 ] (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows that most studies were published in 2020 (n = 7, 20%) [ 23 29 ] and 2021 (n = 6, 17%) [ 30 35 ]. Moreover, most of the studies were conducted in the United States (n = 11, 31%) [ 26 , 34 – 43 ] (Fig. 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in some studies, in order to identify barriers and facilitators, women’s views on all health technologies were obtained. [ 27 , 32 , 34 , 51 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…They disproportionately include those who are rendered vulnerable and disadvantaged in various ways, whether by education, by employment, by birth or by bad luck’ (2018: 940, emphasis added). Women in the justice system may inhabit one of the most precarious positions in terms of the digital divide, when gender, race and socio-economic status are taken into account (Blomberg et al, 2021).…”
Section: The Bi-dimensional and Socio-technical Drivers To Women's Di...mentioning
confidence: 99%
“…Although the argument put forward in this article is theoretical in part, it is also based on sensible assumptions about some of the likely consequences of the court digitisation agenda. Existing research in the field demonstrates that marginalised women offenders are structurally disadvantaged and consequently more likely to be victims of the digital divide (Blomberg et al, 2021; Goedhart et al, 2019; Gurusami, 2018; Seo et al, 2020). They are, at the same time, and by virtue of their status as ‘lesser offenders’ at risk of being more likely to be caught up with the new online systems that are designed to deal with lesser offences.…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that the frequent absence of computers and internet access within prisons constitutes a particular manifestation of wider digital divides (Reisdorf & Jewkes, 2016). This is a continuation of the prevention of communication that has been part of prison life since Victorian times (Jewkes & Johnston, 2009), such prevention took on a heightened significance during the COVID-19 pandemic and lockdown (Blomberg et al, 2021).…”
Section: Critiques Of Goffman's Total Institution and The Increased "...mentioning
confidence: 99%